Epistemology in Islamic Philosophy of Education: Exploring the Sources of Knowledge and Truth in the Qur'an and Hadith - Anggie Ardilla Tari; Mardatul Hasanah; Herlini Puspika Sari (Aslim: Journal of Education and Islamic Studies, 2024)
Epistemology in the philosophy of Islamic religious education focuses on the nature, sources and validation of knowledge, including empirical and revealed knowledge. In the context of Islamic religious education, epistemology plays an important role as a basis for understanding and internalizing Islamic teachings. This research uses literature study methods to explore the concept of Islamic epistemology, especially those related to the Al-Qur'an and Hadith as the main sources of knowledge. The findings show that Islamic education combines naqli (textual) knowledge with aqli (rational) knowledge to shape the spiritual and intellectual character of students. Islamic epistemology not only emphasizes mastery of knowledge, but also the process of moral and spiritual transformation. Through ijtihad, knowledge can develop in accordance with the challenges of the times without sacrificing the core values of Islam. Islamic education prepares students as caliphs on earth, who are not only intellectually intelligent but also have moral integrity. Islamic epistemology is relevant in responding to the challenges of globalization, emphasizing the importance of etiquette in learning, and offering holistic solutions that integrate spirituality and modern science. Knowledge in Islam is not only a tool to achieve worldly success, but also a means of getting closer to Allah.